2016
DOI: 10.5430/jct.v5n2p127
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Accounting and Business Curriculums on Creativity

Abstract: This study employs the Torrance Tests of Creative Thinking to investigate the effects of accounting and business curriculums on students' verbal and figurative creativity via the Solomon four-group design. The subjects are accounting and business administration students in Taiwan, where these two curriculums are similar to their counterparts in the U.S.A. The test scores were analyzed with MANOVA and meta-analysis. The results show that the accounting curriculum has not been as effective as the business admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Most of the previous studies focused on the benefits of the internship program from both students' and employers' perceptions which include the relationship between the internship program, and students' performance, acquisition of knowledge, and improved soft skills. However, the existing literatures also revealed that employers are not satisfied with the employability (or "generic") skills of undergraduate students (Hadiyanto and Ibrahim, 2013;Cheng et al, 2016). Studies highlighted that the existing university curriculum has not sufficiently provided the generic skills such as communication and analytical thinking to students.…”
Section: Introductıonmentioning
confidence: 99%
“…Most of the previous studies focused on the benefits of the internship program from both students' and employers' perceptions which include the relationship between the internship program, and students' performance, acquisition of knowledge, and improved soft skills. However, the existing literatures also revealed that employers are not satisfied with the employability (or "generic") skills of undergraduate students (Hadiyanto and Ibrahim, 2013;Cheng et al, 2016). Studies highlighted that the existing university curriculum has not sufficiently provided the generic skills such as communication and analytical thinking to students.…”
Section: Introductıonmentioning
confidence: 99%
“…Students not only create standard work but must be accompanied by innovative ideas. These innovative ideas are very important to form creativity and originality in a work (Cheng et al, 2016;Lince, 2016;Ritter & Mostert, 2017).…”
Section: Discussionmentioning
confidence: 99%